Trade in information technology products and the WTO agreements : current situation and views of exporters in developing countries (ITC GenevaCH, 1999)
Reviews trade patterns, technological trends and market opportunities for telecommunication and electronic data processing equipment, semi-conductor devices, semiconductor manufacturing equipment and computer software. Examines the impact of WTO Agreements on IT products, manufacturers and exporters in developing countries.
DC